Genome-wide association study identifies 12 new genetic loci associated with growth traits in pigs - Mu Zeng; Binhu Wang; Lei Liu; Yalan Yang; Zhonglin Tang (Journal of Integrative Agriculture, 2024)
Growth traits are among the most important economic traits in pigs and are regulated by polygenes with complex regulatory mechanisms. As the major indicators of growth performance, the backfat thickness (BFT), loin eye area (LEA), and days to 100 kg (D100) traits are commonly used to the genetics improvement in pigs. However, the available genetic markers for these traits are limited. To uncover novel loci and candidate genes associated with growth performance, we collected the phenotypic information of BFT, LEA, and D100 in 1,186 pigs and genotyped all these individuals using the Neogen GGP porcine 80K BeadChip. We performed a genome-wide association study (GWAS) using 4 statistical models, including mixed linear models (MLM), fixed and random model circulating probability unification (FarmCPU), settlement of MLM under progressively exclusive relationships (SUPER), Bayesian-information and linkage-disequilibrium Iteratively nested keyway (Blink), and identified 5, 3, and 6 high-confidence single nucleotide polymorphisms (SNPs) associated with BFT, LEA, and D100, respectively. Variant annotation and quantitative trait locus (QTL) mapping analysis suggested that 6 genes (SKAP2, SATB1, PDE7B, PPP1R16B, WNT3, and WNT9B) were potentially associated with growth performance in pigs. Transcriptome analysis suggested that the expression of Src Kinase Associated Phosphoprotein 2 (SKAP2) was higher in prenatal muscles than in postnatal muscles, and the expression of Phosphodiesterase 7B (PDE7B) continuously increased during the prenatal stages and gradually decreased after birth, implying their potential roles in prenatal skeletal muscle development. Overall, this study provides new candidate loci and genes for the genetic improvement of pigs.